O corpo como espelho do outro: interlocuções entre Merleau-Ponty e Lacan - Santos, Francisco de Assis Bezerra dos (2016)
The body is a key issue for psychoanalysis. For philosophy, found in Merleau-Ponty it's greatest expression, especially in the Phenomenology of Perception. In Lacan, figured as a starting point in his work and amounted to much of his teaching, until the end. Problematize the body seems necessary and imperative, against the trend increasingly reifying of scientific development on the subject and your body. Among the biologizing and the mystical, philosophy and psychoanalysis are fields that make possible the discussion of such a forceful theme without falling into the dissonant aspects of knowledge. The objective of this work is to argue argumentative with Merleau-Ponty and Lacan, as the body itself as correlative to the subject, and how it articulates the formation of the self from this body, marked term in the two thinkers. When using a focused methodology for in-depth reading of the texts and authors and discuss their concepts and assumptions, this dissertation provides an opportunity to realize that these thinkers, each in his field, made it possible or feasible to understanding primary role, fundamental, foundational and mediator body in the experience of man, the subject of the self.